2017
DOI: 10.1111/pere.12198
|View full text |Cite
|
Sign up to set email alerts
|

Work–family conflict, psychological availability, and child emotion regulation: Spillover and crossover in dual‐earner families

Abstract: Work-family balance and child rearing are major social concerns. Few studies, however, have addressed how parents' work-family conflict (WFC) associates with children's emotion regulation. This study proposes the link to occur through parents' psychological availability (PA). In our model we tested both intraindividual and interindividual effects on a sample of 138 dual-earner couples with preschool-aged children. Our results showed that WFC related negatively to PA (actor and partner effects); fathers' and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
55
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 61 publications
6
55
0
2
Order By: Relevance
“…The relationship between the family and work domains has been widely studied in workers as negative interactions between these domains is often associated with negative outcomes for individuals, families, businesses and society, which results in family, job, marital, parental and life dissatisfaction [ 32 , 33 , 34 , 35 , 36 ]. In fact, the level of balance between work and family impacts other life domains and is likely to affect not only the individual parent but also those closest to them [ 33 , 37 ], such as the couple and their children [ 35 ].…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…The relationship between the family and work domains has been widely studied in workers as negative interactions between these domains is often associated with negative outcomes for individuals, families, businesses and society, which results in family, job, marital, parental and life dissatisfaction [ 32 , 33 , 34 , 35 , 36 ]. In fact, the level of balance between work and family impacts other life domains and is likely to affect not only the individual parent but also those closest to them [ 33 , 37 ], such as the couple and their children [ 35 ].…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…Although some structural conditions of parents' work environment (e.g., long working hours, atypical schedules, and husband-wife wage differentials) are associated with parental involvement in dual-earner families (Hook & Wolfe, 2013;Wood & Repetti, 2004;Yeung et al, 2001), the way parents perceive balance between their work and family demands exerts a strong influence on parenting (Cinamon, Weisel, & Tzuk, 2007;Corwyn & Bradley, 1999;Perry-Jenkins, Repetti, & Crouter, 2000;Vieira, Matias, Ferreira, Lopez, & Matos, 2016). Some studies reported that parents' WFC, meaning the experience perceived by the parents as not having enough time and energy to manage all work and family responsibilities, has a negative effect on their psychological availability and socioemotional investment in their children (Matias et al, 2017;Corwyn & Bradley, 1999;Danner-Vlaardingerbroek et al, 2013). The experience of WFC may have particularly negative implications for parents' availability to engage in activities that go beyond basic caretaking, namely spending time with the child in positive engagement activities.…”
Section: Work-family Dynamics and Parental Engagementmentioning
confidence: 99%
“…PARENTAL ENGAGEMENT AND CHILD SELF-CONTROL chological availability, parental self-efficacy, and the quality of parent-child interactions (Matias et al, 2017;Cinamon et al, 2007;Corwyn & Bradley, 1999;Crouter et al, 1999;. Nonetheless, these studies have either been cross-sectional studies or have not focused on the effects of parents' WFC on parental engagement over time.…”
mentioning
confidence: 99%
“…The cross-domain effects occur as employees form an evaluation and judgment on the state of their life based on positive or negative affect from work. Moreover, mothers' work-family conflict undermines their parenting (Matias et al, 2017) and relationship with their children, which, in turn, adversely affects their children's development (Wall, Leitão, & Ramos, 2011). Notably too, spillover can also proceed from family to work; stresses arising from the family can negatively influence an individual's productivity at work (Ford, Heinen, & Langkamer, 2007;Westman, Etzion, & Gattenio, 2008).…”
Section: Theoretical Frameworkmentioning
confidence: 99%